2020
DOI: 10.3389/fimmu.2020.582678
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Proximal Tubule Involvement by BK Polyomavirus in Kidney Transplant Recipients With Urinary Sediment Double-Immunostaining

Abstract: Background: The extent and depth of BK polyomavirus (BKPyV) infection in renal allograft correlate with prognosis. This study was designed to evaluate the value of urinary sediment double-immunostaining for predicting BKPyV infection in proximal tubular epithelium. Materials and methods: A total of 76 urine sediment cell blocks, as well as the corresponding transplanted kidney tissues with BK polyomavirus associatednephropathy (BKPyVAN), were evaluated by automatic double-immunostaining with anti-58-kDa Golgi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Transmission is ongoing from person-to-person, foecal-oral transmission via wastewater is also possible. Furthermore, leukocyte-containing blood transfusion and transplacental transmission has been also reported (4,6). BKV replicates itself in the nucleus of renal tubular proximal epithelial cells that are also the natural host cells (6).…”
Section: Epidemiology and Pathogenesis Of Bkvnmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission is ongoing from person-to-person, foecal-oral transmission via wastewater is also possible. Furthermore, leukocyte-containing blood transfusion and transplacental transmission has been also reported (4,6). BKV replicates itself in the nucleus of renal tubular proximal epithelial cells that are also the natural host cells (6).…”
Section: Epidemiology and Pathogenesis Of Bkvnmentioning
confidence: 99%
“…Furthermore, leukocyte-containing blood transfusion and transplacental transmission has been also reported (4,6). BKV replicates itself in the nucleus of renal tubular proximal epithelial cells that are also the natural host cells (6). Daughter viruses are delivered to other cells to spread infection (7), which is followed by necrosis, inflammation and local tissue damage which enables the virus to penetrate into the intertubular space, peritubular capillaries and adjacent cells (8).…”
Section: Epidemiology and Pathogenesis Of Bkvnmentioning
confidence: 99%
“…An additional suggested urinary test is double staining of shed epithelial cells with anti-58-kDa Golgi protein, expressed on proximal tubules, and SV40. The presence of urinary 58-kDa+/SV40+ cells is strongly correlated with BKVN, with a positive predictive value of 89.7% (95% confidence interval [CI], 71.5%–97.3%) and a negative predictive value of 91.5% (95% CI, 78.7%–97.2%) [ 73 ].…”
Section: Diagnosis Of Polyomavirus Nephropathymentioning
confidence: 99%
“…An epidemiologic study demonstrated that approximately 80% of the general population was infected by BKPyV in their childhood [ 14 ]. Following primary infection, BKPyV is persistently hidden in the renourinary tract, and when the immunity of the organ transplant recipients is suppressed, BKPyV rapidly replicates to cause renal inflammation, the occurrence of BKPy-viruria and BKPy-viremia, and sometimes BKPyV-associated nephropathy (BKPyVAN) [ 15 , 16 , 17 , 18 ]. Potent immunosuppressants reduce acute rejection episodes but increase the risk of BKPyVAN and its associated allograft loss.…”
Section: Introductionmentioning
confidence: 99%